Effects of “sargaço” extraction residues on seed germination - Sousa, Tiago (2021)
Introduction: The “Sargaço” is a mixture of seaweeds that grow on the rocks of the Minho coast and the seaweeds during their development synthesize different metabolites. During the seaweed extraction process, some of these metabolites are not taken, thus not promoting the circular economy. Objectives: This work aimed to evaluate the seed germination potential of the residues discarded from aqueous extraction process of “Sargaço”. Providing a potential use to the undervalued sub product of the extraction it was used bean cv. Methods: Torino (Phaseolus vulgaris) and kale (Brassica oleracea var. acephala) seeds in assays with the following treatments of residues: control (C), “Sargaço” harvested in 2017 with (W) and without the washing process (NW), and the same for the “Sargaço” harvested in 2018 (W and NW). During the experiment, the emergence rate, the germination rate and the total weight difference, were recorded. At the end, the root and shoot length were measured as well as fresh plantlet weight.  Results: In bean, the treatment with washed “Sargaço” 2018 was the only one showing seed germination (C = 60%; W2018 = 32%) beyond the control and with better results in the radicular weight than control (C= 0,0350 g; W2018= 0,299 g). In kale, only the washed “sargaço” 2017 had a germination rate like the control (C=80%, W2017=64%) and the overall weight was better (C= 0,0026 g, W2017= 0,0102 g). Conclusions: The washed residues produced the best results comparatively which is probably due to the higher salinity of the unwashed residues.